Causes and Control Measures of Apple Replant Problem - Sharma, N. C.; Verma, Pramod; Singh, Niranjan; Babita (International Journal of Bio-resource and Stress Management, 2020)
Replant problem is a situation resulting in suppression of growth and poor productivity of the trees planted on old orchard sites and makes the plantations un-economical. It is a serious malady throughout the world in some fruit crops where the new plantations are done at the old orchard sites. Although replant problem is known to exist for many decades but greater attention was paid to this phenomenon only when Thompson (1959) while working at East Malling Research Station, United Kingdom observed poor growth of apple and cherry on old plantation sites. This observation strongly stimulated replant research in different parts of the world. Western Himalayan states of India are also facing the replant problem where majority of apple orchards have out lived their economic life and new plantations are being done at the same site. The incidence of apple replant disease on various sites has been observed 25-70 per cent. It is comparatively easy to prevent the replant problem than to control it because of unknown exact etiology and complex nature of malady due to the presence of different biotic and abiotic factors associated with the problem. Nature and intensity of the incidence is highly variable from country to country and even region to region and there is lack of quick diagnostic methods. The problem is difficult to control with one method and require integrated management practices for effective control.